Bioactive Compound from Extract Filtrat Streptomyces sp.Sp1. as Biocontrol of Vibriosis on Larvae of Macrobrachium rosenbergii shrimps - Retno Kawuri; IBG Darmayasa (Bogor Agricultural University, Indonesia, 2019)
Production of Macrobrachium rosenbergii shrimp was limited by vibriosis disease. Streptomyces can be used as an alternative control of vibriosis which is caused by Vibrio anguillarum. Aplication of Streptomyces sp.1 culture could give significant different impacts (p<0.05) on the percentage of survival (SR) of shrimp larvae that had been infected by V. anguillarum compared to the control. This study was conducted to identify and determine bioactive compound of Streptomyces sp.1. The presence of bioactive compound was confirmed by gas chromatography-mass spectrometry (GC-MS) analysis. Identification of Streptomyces sp.1 by 16S rRNA partial gene sequencing method. Streptomyces sp.1 was identified to be Streptomyces sp.Sp1. There were 35 chemical compounds identified, the chemical compounds which have antimicrobial properties identified in the n butanol extract of Streptomyces sp.Sp1 are 3-Hexanone, 2-methyl (43%), n Butyl ether (19%) Nonane (CAS) n-Nonane (5.6%), Decane (CAS) n-Decane (3.2%), Hexacosane (CAS) n-Hexacosane (1.9%), Tetracontane (1.3%), Heneicosane (1.9%), Hexadeconoic acid, methyl ester (0.3%), Butane,1,1-dibutoxy (0.3%), and Limonene (0.3%). Benzeneacetic acid, 3-methoxy-.alpha.,4-bis[(tri (0.3%). These results suggested that Streptomyces sp.Sp1 had good general antimicroba activity and might have potential biocontrol antagonist Vibrio anguillarum.